LL-37 as a Powerful Molecular Tool for Boosting the Performance of Ex Vivo-Produced Human Dendritic Cells for Cancer Immunotherapy - Stakheev, Dmitry; Taborska, Pavla; Kalkusova, Katerina; Bartunkova, Jirina; Smrz, Daniel (Pharmaceutics, 2022)
Ex vivo-produced dendritic cells (DCs) constitute the core of active cellular immunotherapy (ACI) for cancer treatment. After many disappointments in clinical trials, the current protocols for their preparation are attempting to boost their therapeutic efficacy by enhancing their functionality towards Th1 response and capability to induce the expansion of cytotoxic tumor-specific CD8+ T cells. LL-37 is an antimicrobial peptide with strong immunomodulatory potential. This potential was previously found to either enhance or suppress the desired anti-tumor DC functionality when used at different phases of their ex vivo production. In this work, we show that LL-37 can be implemented during the whole process of DC production in a way that allows LL-37 to enhance the anti-tumor functionality of produced DCs. We found that the supplementation of LL-37 during the differentiation of monocyte-derived DCs showed only a tendency to enhance their in vitro-induced lymphocyte enrichment with CD8+ T cells. The supplementation of LL-37 also during the process of DC antigen loading (pulsation) and maturation significantly enhanced the cell culture enrichment with CD8+ T cells. Moreover, this enrichment was also associated with the downregulated expression of PD-1 in CD8+ T cells, significantly higher frequency of tumor cell-reactive CD8+ T cells, and superior in vitro cytotoxicity against tumor cells. These data showed that LL-37 implementation into the whole process of the ex vivo production of DCs could significantly boost their anti-tumor performance in ACI.
Keywords: cancer; LL-37; CD8+ T cells; cellular immunotherapy; dendritic cells